The Arabidopsis-Trichoderma interaction reveals that the fungal growth medium is an important factor in plant growth induction. Issue 1 (December 2018) - González-Pérez, Enrique; Ortega-Amaro, María; Salazar-Badillo, Fatima; Bautista, Elihú; Douterlungne, David; Jiménez-Bremont, Juan
Abstract Trichoderma spp colonizes the plant rhizosphere and provides pathogen resistance, abiotic stress tolerance, and enhance growth and development. We evaluated the Arabidopsis-Trichoderma interaction using a split system in whichTrichoderma atroviride andTrichoderma virens were grown on PDA or MS medium. Arabidopsis growth was significantly increased at 3 and 5 days post-inoculation with both Trichoderma species, when the fungal strains were grown on PDA in split interaction. The analysis ofDR5:uidA reporter line revealed a greater auxin accumulation in root tips when the fungi were grown on PDA in a split interaction. The root hair-defective phenotype of Arabidopsisrhd6 mutant was reverted with both Trichoderma species, even in split interactions. At 12 °C, Trichoderma species in split interactions were able to mitigate the effects of cold stress on the plant, and also Trichoderma induced theAtERD14 expression, a cold related gene. Volatile organic compounds analysis revealed that Trichoderma strains produce mainly sesquiterpenes, and that the type and abundance of these compounds was dependent on the fungal strain and the culture medium. Our results show that fungal nutrition is an important factor in plant growth in a split interaction.